2017
DOI: 10.1123/ijsc.2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

Disabling Prejudice: A Case Study of Images of Paralympic Athletes and Attitudes Toward People With Disabilities

Abstract: Part of the goal of the International Paralympic Committee is to “touch the heart of all people for a more equitable society” by exposing people to adaptive sports, with the goal of improving public views toward people with disabilities. The authors hypothesized that exposure to parasocial contact with images of athletes with disabilities could lead to a change in attitude during the formation of social identity, disrupting the tendency to view the population of individuals with physical disabilities as “other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Positive emotion of PWDs can impact attitudes toward PWDs (Suggs & Guthrie, 2017). Some studies (Chebat & Slusarczyk, 2005;Donada & Nogatchewsky, 2009) have shown that an intervention that evoked positive emotions resulted in positive attitudes toward PWDs.…”
mentioning
confidence: 99%
“…Positive emotion of PWDs can impact attitudes toward PWDs (Suggs & Guthrie, 2017). Some studies (Chebat & Slusarczyk, 2005;Donada & Nogatchewsky, 2009) have shown that an intervention that evoked positive emotions resulted in positive attitudes toward PWDs.…”
mentioning
confidence: 99%
“…, 2018; Cottingham et al. , 2014; Suggs and Guthrie, 2017) and can positively influence spectating intention, especially for those unfamiliar with disability sport (Yamashita and Muneda, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This balanced marketing rationale was recommended in previous research on disability sport practitioners' promotion strategies (Cottingham et al, 2013(Cottingham et al, , 2015a, and based on the knowledge that spectators internalize the athleticism versus supercrip narrative differently (Byon et al, 2010;Chatfield and Cottingham, 2017;Cottingham et al, 2015a). Notwithstanding, inspiration does elicit positive responses from consumers (Bartsch et al, 2018;Cottingham et al, 2014;Suggs and Guthrie, 2017) and can positively influence spectating intention, especially for those unfamiliar with disability sport (Yamashita and Muneda, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…One of the goals of the International Paralympic Committee is to “touch the heart of all people for a more equitable society” by exposing people to adaptive sports, with the goal of improving the public perception of disabled persons (Suggs & Guthrie, 2017, p. 258). Suggs and Guthrie (2017) added that “. .…”
Section: Methods and Data Collectionmentioning
confidence: 99%